The development of code detection on personalization in E-commerce website / Norhafifah Jasman - Jasman, Norhafifah (Faculty of Computer and Mathematical Sciences, 2006)
Personalization in E-commerce website today is concerned to personalizing their customer and customizing customer's interest. Many personalization approach and technique is designed to meet customers' requirements. Since personalization approach wide used by e-commerce websites, no proper tool that can determine the quality of personalization that offered by e-commerce website. This research is discussed about the Development of Code Detection of personalization of ecommerce website. This development is concerned to personalization criteria that was implementing in various e-commerce website nowadays. The research is done only on PHP e-commerce websites. Wu Framework is used as a guideline to analyzing different type of personalization criteria and coding scheme for categorizing the personalization criteria. The process development is done by followed SDLC concept and Personalization Automation Tool (PAT) is developed. PAT is a software tool that developed for verification of personalization criteria in e-commerce websites. The development of PAT focuses on two criteria which are anthropomorphic personalization and link personalization (bookmark). There are several methods and procedure used in the research. PAT is developed to detect the personalization criteria which are implemented in PHP e-commerce websites. This tool development can be a commercial product for e-commerce companies to verify quality of functionality on personalization in their e-commerce websites. Finally, customer satisfaction is achieved that assumed as a necessary condition for the success of organizations.